ANALISIS PENGARUH DISTRESS RISK, FIRM SIZE, BOOK TO MARKET RATIO, RETURN ON ASSETS, DAN DEBT EQUITY RATIO TERHADAP RETURN SAHAM - Husein, Ferhat; Mahfud, M. Kholiq (Diponegoro Journal of Management, 2015)
The purpose of this research is to examine the influence of Distress Risk, Firm Size, Book to Market Ratio (BMR), Return On Assets (ROA), and Debt to Equity Ratio (DER) to stock return. This research used the Corporate data which have gone public and listed it to Indonesian Stock Exchange and classified with index Lq45. The data that it used at this research came from the annual published financial report of Indonesian Capital Market Directory period 2009-2013 with 25 corporate sampleThe method that used in this research was multiple regression analysis and then used assumption classic test and used hypothesis test that including F-statistic, T-statistic and determination of coefficients (R2).            The results of this research shows that distress risk have positive influence but not significant to stock return , size has a negative influence and has significant influence to stock return, BMR have a negative influence and have significant influence to stock return, ROA and DER does not have significant influence to stock return